Understanding The Role of Materialism on The Relationship Between Advertising and Compulsive - Randikaparsa, Irawan; Anggara, Ali Akbar; Suparno, Chandra; Rafinda, Ascariena (Universitas Negeri Semarang, 2022)
To academics and policymakers. This study is to examine the effect of Advertising on compulsive purchasing and materialism as mediating variables in Purwokerto. Using the snowball sampling technique, 450 samples were gathered from various areas of the city of Purwokerto, Indonesia. This research employs PLS. The promotion was statistically significant at 5% and had a positive link with materialism in Purwokerto, Indonesia, according to the findings. Similarly, materialism was found to be statistically significant and favourable in 95% of compulsive buyers. , materialism influences the connection between advertising and compulsive purchasing. The study suggests that it is essential to prioritize these elements.